2018
DOI: 10.1177/0363546518777247
|View full text |Cite
|
Sign up to set email alerts
|

Bone Bruise Patterns in Skeletally Immature Patients With Anterior Cruciate Ligament Injury: Shock-Absorbing Function of the Physis

Abstract: The data from this study shows that patients with an open physis at the occurrence of an acute ACL rupture have unique bone bruise patterns as compared with those with a closed physis. In the SI patients, the bone bruise pattern is significantly less frequently observed in the tibial and femoral metaphysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…An important finding of this study was that pediatric and adult patients display similar bone bruise localization, 22 which is in contrast with previous evidence showing that patients with open physes at the occurrence of an acute ACL rupture have unique bone bruise patterns compared with those with closed physes. 29 As reported in the Results section, the lateral central femur and the lateral posterior tibia were the areas most commonly affected by bone bruises in the pediatric patients included in this study; as reported by Filardo et al, 6 these are also the areas most commonly affected by bone bruises in adults. This finding indicates that the mechanisms that lead to ACL tears are the same regardless of age.…”
Section: Discussionsupporting
confidence: 72%
“…An important finding of this study was that pediatric and adult patients display similar bone bruise localization, 22 which is in contrast with previous evidence showing that patients with open physes at the occurrence of an acute ACL rupture have unique bone bruise patterns compared with those with closed physes. 29 As reported in the Results section, the lateral central femur and the lateral posterior tibia were the areas most commonly affected by bone bruises in the pediatric patients included in this study; as reported by Filardo et al, 6 these are also the areas most commonly affected by bone bruises in adults. This finding indicates that the mechanisms that lead to ACL tears are the same regardless of age.…”
Section: Discussionsupporting
confidence: 72%
“…Although a 6week threshold has commonly been used in the literature, the 4-week threshold was selected to further minimize timing errors 12 and preserve the signal characteristics of bone bruises. Given that skeletally immature patients demonstrate unique bone bruise patterns, 23 and bone mineral density decreases gradually in patients aged >40 years, 13 which could affect the signal characteristics of a bone bruise, only those aged 18 to 40 years were selected. The exclusion criteria included (1) previous trauma to the affected knee, (2) posterior cruciate ligament injuries, (3) medial or lateral collateral ligament injuries, and (4) absent or poor-quality MRI scans ( Figure 1).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Femoral and tibial bone bruises are thought to represent a footprint of impact at the time of the injury, offering insight into the mechanisms of an ACL injury. 29,32,33 Previous studies have reported that the most common patterns observed in an ACL injury were bone bruises in the lateral compartment, 23,29 which indicated that the valgus load was the primary mechanism of an ACL injury. 20 Other studies reported that anterior tibial translation with a small knee flexion angle may be the primary mechanism of an ACL injury based on the observed bone bruises on the posterior tibia and anterior femur.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the recent literature regarding posterolateral tibial plateau injury in the setting of an ACL tear has focused on bone bruises, sometimes described as occult or nondisplaced impaction fractures. 1,3,8,9,15,16 Bone bruising in the setting of ACL tear has a reported incidence of approximately 80%. 1,13 When bone bruising is present, it suggests a higher energy pivoting injury, as full or high-grade partial ACL tears are more frequently associated with bone bruising compared with low-grade partial tears.…”
mentioning
confidence: 99%